2010
DOI: 10.1523/jneurosci.5709-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Sensorimotor Function after Experimental Stroke Correlates with Restoration of Resting-State Interhemispheric Functional Connectivity

Abstract: Despite the success of functional imaging to map changes in brain activation patterns after stroke, spatiotemporal dynamics of cerebral reorganization in correlation with behavioral recovery remain incompletely characterized. Here, we applied resting-state functional magnetic resonance imaging (rs-fMRI) together with behavioral testing to longitudinally assess functional connectivity within neuronal networks, in relation to changes in associated function after unilateral stroke in rats. Our specific goals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
293
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 312 publications
(340 citation statements)
references
References 51 publications
43
293
0
4
Order By: Relevance
“…In agreement with our previous study (van Meer et al, 2010), interhemispheric functional connectivity…”
Section: Interhemispheric Connectivitysupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with our previous study (van Meer et al, 2010), interhemispheric functional connectivity…”
Section: Interhemispheric Connectivitysupporting
confidence: 93%
“…In line with our previous study (van Meer et al, 2010), we found a significant increase in intrahemispheric functional connectivity within the contralesional sensorimotor cortex in rats with a relatively large unilateral infarction in the opposite (ipsilesional) sensorimotor network. In addition, we detected increased accumulation of the neuronal tracer manganese within the contralesional sensorimotor cortex of rats with large unilateral ischemic lesions, which suggests that the increase in functional connectivity is related to stronger local neuroanatomical association.…”
Section: Intrahemispheric Connectivitysupporting
confidence: 93%
See 3 more Smart Citations